Guidance for use of weights: an analysis of different types of weights and their implications when using SAS PROCs. Issue 1 (20th February 2019) - Richardson, Sabrina; Lin, Tuo; Li, Yangyi; Niu, Xiaohui; Xu, Manfei; Stander, Valerie; Tu, Xin M
Abstract : SAS and other popular statistical packages provide support for survey data with sampling weights. For example, PROC MEANS and PROC LOGISTIC in SAS have their counterparts PROC SURVEYMEANS and PROC SURVEYLOGISTIC to facilitate analysis of data from complex survey studies. On the other hand, PROC MEANS and many other classic SAS procedures also provide an option for including weights and yield identical point estimates, but different standard errors (SEs), as their corresponding survey procedures. This paper takes an in-depth look at different types of weights and provides guidance on use of different SAS procedures.